REFLECTION ON EFFICIENCY IN PUBLIC HEALTH ADMINISTRATION: AN INTEGRATIVE LITERATURE REVIEW (CIPEEX, 2025)
Public health planning is essential to guide strategic management decisions and ensure the effective use of available resources. In a scenario of limited resources and growing demands, optimizing the allocation and administration of these resources becomes crucial in order to generate public value and maximize the impact on the population's health. This study aims, through an integrative literature review, to explore theories that elucidate the relationship between efficient management and health promotion in the public sector. The literature review was conducted using a computerized search of the CAPES journal portal and the LILACS and SciELO databases. Articles published between 2020 and 2024 were included, in English and Portuguese, based on the descriptors: Efficiency, Governance, Management and Public Health. Resources that did not correspond to scientific articles were excluded, as well as those that were not aligned with the focus of this research, resulting in the selection of 11 studies. The results of the study reveal a duality faced by public managers in their quest for efficiency. On the one hand, legislation demands maximum efficiency in public operations and services. On the other, organizational culture often fails to keep up with changes and the real needs of society. In relation to the articles analyzed, it was observed that quality and efficiency in public administration are associated with a particular understanding of people, who use specific criteria to evaluate and add value to government actions. The conclusion is that the search for quality and efficiency is vital in the field of public health in order to achieve positive results. This requires effective management of resources, with competent professionals in the sector and skilled leaders to manage public health networks.
Keywords: efficiency; governance; management; public health